PENGARUH IMPLEMENTASI AMANDEMEN MEMORANDUM OF UNDERSTANDING (MoU) KETENAGAKERJAAN 2006 INDONESIA-MALAYSIA TERHADAP PENGIRIMAN TENAGA KERJA INDONESIA (TKI) KE MALAYSIA TAHUN 2012-2014 - Irfani, Rezwita; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research aims to explain influence of implementation of the amendment of Memorandum of Understanding (MoU) employment 2006 Indonesia-Malaysia on the sending of Tenaga Kerja Indonesia (TKI) to Malaysia in 2012-2014. The number of jobs which was not equivalent to the number of Indonesian population causes many TKI work abroad. Malaysia as one of the main destinations of TKI has its own problems related to cases of human rights violations which were suffered by the workers there. The moratorium issued by Indonesian government was a response to the case of human rights violations, but in December 2011, the government revoked the moratorium and carried out protocol amending the Memorandum of Understanding (MoU) 2006. The sources of this research are obtained through literature review, other books, website, etc.The sources analysis is qualitative methode. This research uses a level analysis of nation state, Liberalism perspective, and also using theory of interdepedence. The results of this research shows that the Implementation of Amendment of MoU 2006 has ratified granting of the rights of Indonesian migrant workers, reducing number of unemployed people in Indonesia with the continuing delivery of Indonesian migrant workers to Malaysia, increasing acceptance of remittances from migrant workers in Malaysia and also number of migrant workers legal in Malaysia, forming a joint task force between Indonesia and Malaysia, and fixing law governing on protection of indonesian migrant workers. Key Words: Amendment of Memorandum of Understanding 2006, Indonesian Migrant Workers, International Coorperation, Remittance, Joint Task Force.